Life-Long Learning Profile of Junior High School Students in Science Learning - Nikmah, Citra Khoerun; Hayat, M. Syaipul; Patonah, Siti (Jurnal Pijar Mipa, 2025)
Implementing life-long learning is vital to help students face rapid global development. Life-long learning is a principle in organizing education and a primary need for everyone to adapt to changing times. This study aims to analyze the application level of lifelong learning among SMP Negeri 1 Pucakwangi students, especially class VII students. This study used a descriptive qualitative approach with a sample of 28 students. Data were collected through a questionnaire containing five life-long learning indicators: complex thinking, information processing, effective communication, collaboration/cooperation, and habits of mind. The results showed that overall, the level of life-long learning application of students at SMP Negeri 1 Pucakwangi was still in the poor category, with an average score of 2.8 out of a 4.0 scale. Students obtained a high score (3.0) in the complex thinking indicator. In contrast, in other indicators, such as information processing (2.7), effective communication (2.6), collaboration/cooperation (2.8), and habits of mind (3.1), the scores obtained were still relatively low. The three indicators that obtained low scores, namely information processing, effective communication, and collaboration/cooperation, indicate that students still need further development in these skills. Based on the study results, it can be concluded that although some indicators show good results, there are also indicators that need to be improved to optimize the implementation of lifelong learning. Therefore, there is a need for further efforts in improving students' skills, especially in terms of information processing, effective communication, and collaboration, so that they can be better prepared to face the growing global challenges.